Lignol to Collaborate with Weyerhaeuser to Explore Commercial Development of Cellulose-based Products and Biochemicals (Canada NewsWire, 2008)
Certain statements contained in this document may constitute forward-looking information within the meaning of applicable securities laws. Such forward-looking statements or information include, without limitation, statements or information about the planning and development of our cellulosic ethanol commercial demonstration plant in Colorado, our ability to exploit commercial opportunities and broaden our market opportunities for a range of cellulosic derivatives and environmentally sustainable biochemicals and our ability to pursue these opportunities with strategic partners. Often, but not always, forward-looking statements or information can be identified by the use of words such as "plans", "expects" or "does not expect", "is expected", "budget", "scheduled", "estimates", "forecasts", "intends", "anticipates" or "does not anticipate", or "believes" or variations of such words and phrases or words and phrases that state or indicate that certain actions, events or results "may", "could", "would", "might" or "will" be taken, occur or be achieved. Such statements or information reflect Lignol's current views with respect to future events and are subject to certain risks, uncertainties and assumptions, including, without limitation, our ability to finance the development of the commercial demonstration plant, our ability to develop our products, our ability to obtain requisite regulatory approvals and our ability to enter into agreements with strategic partners on terms acceptable to us. Forward-looking statements and information are necessarily based upon a number of estimates and assumptions that, while considered reasonable by management, are inherently subject to significant business, economic and competitive uncertainties and contingencies. Many factors could cause Lignol's actual results, performance or achievements to be materially different from any future results, performance or achievements that may be expressed or implied by such forward-looking statements or information, including among other things, the complexity of the development of the commercial demonstration plant, market conditions which will effect our ability to finance our operations, risks relating to the protection of Lignol's core technology from infringement and those risk factors which are discussed elsewhere in documents that Lignol files from time to time with securities regulatory authorities.